A high-temperature non-aging iron powder core and preparation method thereof
By acidifying and modifying the reduced iron powder and mixing it with high-temperature insulating agent, a high-temperature non-aging iron powder core is formed, which solves the problems of high magnetic loss and short life of the iron powder core in high-frequency motors, and achieves high resistivity and low resistance Loss and long life performance, suitable for permanent magnet motors.
Patent Information
- Application Number
- CN202111595687.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-12-24
AI Technical Summary
The existing iron powder cores have problems such as high magnetic loss, low resistivity, poor fluidity and short service life in high-frequency motors, which are difficult to meet the requirements of high resistivity, high magnetic permeability, miniaturization and low loss of permanent magnet motors. .
Reduced iron powder is used for acidification modification pretreatment, mixed with high-temperature insulator and binder, pressed into an iron powder core, and then coated with epoxy resin paint to form a high-temperature non-aging iron powder core, which improves resistivity and magnetic conductivity rate, reduce loss.
The iron powder core with high resistance, stable magnetic permeability, low loss and long life can be achieved, which can operate continuously and stably at high temperatures, reduce eddy current losses, extend service life, and is low in cost and environmentally friendly.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic components, and in particular to a high-temperature non-aging iron powder core and a preparation method thereof. Background Art
[0002] Iron powder core is a common magnetic material in the field of electronic components. It is widely used because of its low price, excellent DC superposition performance and high electromagnetic performance. In recent years, in order to adapt to the development trend of low-carbon economy, permanent magnet motors have gradually developed in the direction of high efficiency, miniaturization and high frequency. In the field of traditional high-frequency motors, iron, silicon and nickel alloy materials are generally used to make motors to obtain high-frequency motors with high frequency, high magnetic permeability and low loss. However, since eddy current loss is difficult to be effectively controlled and heat loss remains high, the motor performance is difficult to meet high-frequency requirements. Iron powder core is widely used to manufacture miniaturized, high-frequency, energy-saving and environmentally friendly motors due to its high magnetic permeability, high resistivity and low loss.
[0003] In the prior art, the iron powder core belongs to ferromagnetic materials, which have high magnetic flux and high magnetic permeability, but have the defects of low resistivity and large magnetic loss, which makes it difficult to meet the production requirements of high resistivity, high magnetic permeability, miniaturization and low loss of permanent magnet motors. The core loss mainly refers to the eddy current loss and hysteresis loss of the core. The stress of the traditional iron powder core is not completely eliminated below 200°C, resulting in high hysteresis loss. In addition, the defects such as low resistance, high eddy current loss and large magnetic loss caused by insufficient insulation of the core lead to a significant decrease in the service life of the device, which makes it difficult to meet the working requirements of the existing motor. Chinese patent CN1167990A discloses an iron powder core, iron powder for the iron powder core and a method for preparing the iron powder core. The method adopts an organic-inorganic composite insulation method to obtain a high temperature resistant insulating coating film, solidifies at 50-250°C, presses the powder into blocks, and anneals in an inert atmosphere at 550-650°C to obtain the iron powder core. Although it can operate at a higher temperature, it has the defects of poor fluidity, large high-frequency loss and low service life. Therefore, in order to ensure that the motor has excellent operating performance, it is necessary to develop an iron powder core with low loss, high resistivity, high magnetic properties, and long high temperature operating life. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-temperature non-aging iron powder core and a preparation method thereof, which uses reduced iron powder as the main raw material, performs acid modification pretreatment on it, and then mixes it evenly with a high-temperature insulating agent and a high-temperature adhesive, and then presses it into an iron powder core. The prepared iron powder core is coated with epoxy resin paint to obtain the high-temperature non-aging iron powder core, which gives the present invention the characteristics of high resistance, stable magnetic permeability, and low loss, and can operate stably and permanently at high temperatures.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] On the one hand, the present invention provides a high-temperature non-aging iron powder core, which is mainly made of the following raw materials:
[0007] 100-500 parts by weight of reduced iron powder, 10-100 parts by weight of mixed acid solution, 1-10 parts by weight of inorganic high-temperature insulating agent, 10-200 parts by weight of inorganic high-temperature adhesive, 10-100 parts by weight of organic silane coupling agent, 10-50 parts by weight of lubricant, 1-20 parts by weight of epoxy resin paint, and 10-200 parts by weight of water.
[0008] Furthermore, the reduced iron powder has a purity of 95% or more, specifically, the reduced iron powder has a purity of 98% or more, and preferably, the reduced iron powder has a purity of 99% or more.
[0009] Further, the particle size of the reduced iron powder is 50-500 mesh, specifically, the particle size of the reduced iron powder is 100-400 mesh, preferably, the particle size of the reduced iron powder is 100-300 mesh.
[0010] Furthermore, in terms of mass percentage concentration, the mixed acid solution is composed of 0.5-5% phosphoric acid, 0.01-1% oxidant and 0.001-0.05% organic acid. Specifically, the mixed acid solution is composed of 0.5-3% phosphoric acid, 0.01-0.5% oxidant and 0.001-0.03% oxalic acid. Preferably, the mixed acid solution is composed of 0.5-2% phosphoric acid, 0.01-0.1% oxidant and 0.001-0.02% oxalic acid.
[0011] Furthermore, the oxidant is a combination of at least one of nitric acid, chromic acid, hydrogen peroxide, potassium permanganate, sodium hypochlorite, and ozone. Specifically, the oxidant is a combination of at least one of nitric acid, chromic acid, hydrogen peroxide, and potassium permanganate. Preferably, the oxidant is a combination of at least one of nitric acid, chromic acid, and hydrogen peroxide.
[0012] Further, the organic acid includes a combination of at least one of oxalic acid, citric acid, malic acid, acetic acid, ascorbic acid, and butyric acid. Specifically, the organic acid includes a combination of at least one of oxalic acid, citric acid, malic acid, and acetic acid. Preferably, the organic acid includes a combination of at least one of oxalic acid, citric acid, and malic acid.
[0013] Further, by weight, the phosphoric acid is 0.1-3.0% of the reduced iron powder, specifically, the phosphoric acid is 0.1-1.0% of the reduced iron powder, preferably, the phosphoric acid is 0.1-0.8% of the reduced iron powder.
[0014] Further, by weight, the organic acid is 0.001-0.05% of the reduced iron powder, specifically, further, the organic acid is 0.001-0.03% of the reduced iron powder, preferably, the organic acid is 0.001-0.01% of the reduced iron powder.
[0015] Further, the inorganic high-temperature insulating agent is a combination of at least one of yttrium oxide, zirconium oxide, holmium oxide, cerium oxide, tantalum oxide, titanium oxide, silicon oxide, aluminum oxide, etc. Specifically, the inorganic high-temperature insulating agent is a combination of at least one of yttrium oxide, zirconium oxide, cerium oxide, holmium oxide, tantalum oxide, etc. Preferably, the inorganic high-temperature insulating agent is a combination of at least one of yttrium oxide, zirconium oxide, cerium oxide, etc.
[0016] Further, the inorganic high temperature binder is composed of at least one of alumina, silica, boron oxide, magnesium oxide, zirconium oxide, zinc oxide, and calcium aluminate. Specifically, the inorganic high temperature binder is composed of at least one of alumina, silica, boron oxide, zinc oxide, and zirconium oxide. Preferably, the inorganic high temperature binder is composed of at least one of alumina, silica, and zirconium oxide.
[0017] Further, the lubricant includes at least one of zinc stearate, graphite powder, mica, talcum powder, barium hydroxide, and borax. Specifically, the lubricant includes at least one of zinc stearate, graphite powder, mica, and borax. Preferably, the lubricant includes at least one of zinc stearate, graphite powder, and mica.
[0018] On the other hand, the present invention provides a method for preparing a high-temperature non-aging iron powder core, comprising the following steps:
[0019] 1) Weigh the reduced iron powder according to the weight ratio, pour a certain weight of water into it, and stir to moisten it;
[0020] 2) Add the mixed acid solution to the material obtained after wetting in step 1), stir evenly, heat and react for a period of time, and then stir-fry the iron powder until dry;
[0021] 3) Add water to step 2), stir to fully wet, then add inorganic high temperature insulating agent, stir until mixed evenly, then add inorganic high temperature binder, stir to mix evenly, then add organic silane coupling agent, continue to stir until dry, add lubricant, continue to stir until mixed evenly, to obtain a mixture;
[0022] 4) pressing the mixture obtained in step 3) into an iron powder core;
[0023] 5) annealing the iron powder core obtained in step 4), cooling it to room temperature and then vibrating and grinding it to remove burrs;
[0024] 6) Spray epoxy resin paint on the iron powder core obtained in step 5), and after drying, obtain the high temperature non-aging iron powder core.
[0025] Further, the amount of water used in step 1) is 1 / 10-1 / 3 of the reduced iron powder, specifically, the amount of water used in step 1) is 1 / 10-1 / 5 of the reduced iron powder, preferably, the amount of water used in step 1) is 1 / 10-1 / 8 of the reduced iron powder.
[0026] Further, the temperature after heating in step 2) is 80-200°C, specifically, the temperature after heating in step 2) is 80-190°C, preferably, the temperature after heating in step 2) is 100-180°C.
[0027] Furthermore, the reaction time of step 2) is 1-10 hours, specifically, the reaction time of step 2) is 2-8 hours, preferably, the reaction time of step 2) is 4-6 hours.
[0028] Furthermore, in step 3), the concentration of the inorganic high temperature binder is 0.5-5.0%. Specifically, the concentration of the inorganic high temperature binder in step 3) is 0.5-3.0%. Preferably, the concentration of the inorganic high temperature binder in step 3) is 0.5-2.0%.
[0029] Furthermore, the pressing pressure in step 4) is 5-20 T / cm 3 Specifically, the pressing pressure in step 4) is 7-15T / cm 3 Preferably, the pressing pressure in step 4) is 8-12T / cm 3 .
[0030] Further, the annealing temperature in step 5) is 100-300°C, specifically, the annealing temperature in step 5) is 100-250°C, preferably, the annealing temperature in step 5) is 150-250°C.
[0031] Further, the annealing heat treatment time in step 5) is 1-8 hours, specifically, the annealing heat treatment time in step 5) is 1-5 hours, preferably, the annealing heat treatment time in step 5) is 2-4 hours.
[0032] Further, the vibration time in step 5) is 10-120 minutes, specifically, the vibration time in step 5) is 20-90 minutes, preferably, the vibration time in step 5) is 30-60 minutes.
[0033] Further, the epoxy resin paint film thickness in step 6) is 0.1-0.5mm, specifically, the epoxy resin paint film thickness in step 6) is 0.1-0.5mm, preferably, the epoxy resin paint film thickness in step 6) is 0.1-0.3mm.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The present invention performs a passivation pretreatment on the reduced iron powder in a mixed acid solution to form a uniform insulating film on the surface of the reduced iron powder, thereby increasing the resistance of the iron powder core and reducing the accelerated aging of the present invention due to temperature rise during operation;
[0036] 2. By adding an inorganic high-temperature insulating agent and an inorganic high-temperature binder, a high-temperature insulating layer is wrapped around the reduced iron powder particles to form a large number of insulating iron powder particles, which further endows the present invention with high resistivity, high magnetic flux density, low loss and excellent high-temperature resistance, ensuring that the present invention does not generate eddy current loss and does not age due to high temperature;
[0037] 3. The inorganic high-temperature insulating agent and inorganic high-temperature binder used in the present invention enable the iron powder to be firmly bonded at high temperatures, further ensuring that the magnetic properties of the iron powder core will not be greatly reduced when working at high temperatures, thereby maintaining stable, lasting, high permanent magnetic properties and a long service life of the present invention;
[0038] 4. The resistivity of the present invention is 65μΩ.m, the magnetic flux density (10kA / m) is 1.8T, and the iron loss (f=50Hz, Bm=1.0T) is less than 40 mw / cm 3 ;
[0039] 5. Water is used as a solvent in the preparation process of the present invention, which has low cost, does not generate organic pollution, and is environmentally friendly. DETAILED DESCRIPTION
[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] A method for preparing a high-temperature non-aging iron powder core comprises the following steps:
[0043] 1) Weigh 220 parts by weight of reduced iron powder, add 20 parts by weight of pure water, and stir to moisten;
[0044] 2) Add 50 parts by weight of a mixed acid solution containing 0.5% phosphoric acid, 0.03% nitric acid and 0.005% oxalic acid, stir evenly, react for 4 hours, and at the same time raise the temperature to 120°C, stir-fry the iron powder until dry;
[0045] 3) Add 30 parts by weight of pure water, stir and wet thoroughly, then add 1.3 parts by weight of zirconium oxide powder, stir until well mixed, then add 60 parts by weight of 0.8% sodium silicate aqueous solution, stir and mix, then add 30 parts by weight of silane A151, continue to stir fry until dry, add 15 parts by weight of zinc stearate, continue to stir until well mixed;
[0046] 4) Mix the mixture at 8.0T / cm 3 The pressure is pressed into an iron powder core;
[0047] 5) Heat the iron powder core to 180°C, anneal for 2 hours, cool to room temperature, and vibrate for 30 minutes to remove burrs;
[0048] 6) Spray epoxy resin paint on the iron powder core with a paint film thickness of 0.15 mm to obtain the non-aging iron powder core.
[0049] Example 2
[0050] A method for preparing a non-aging iron powder core comprises the following steps:
[0051] 1) Weigh 280 parts by weight of reduced iron powder, add 30 parts by weight of pure water, and stir to moisten;
[0052] 2) Add 70 parts by weight of a mixed acid solution containing 0.8% phosphoric acid, 0.05% nitric acid, and 0.008% oxalic acid, stir evenly, react for 5 hours, and heat to 150°C at the same time, stir-fry the iron powder until dry.
[0053] 3) Add 50 parts by weight of pure water, stir and wet thoroughly, then add 1.5 parts by weight of zirconium oxide powder, stir until well mixed, then add 80 parts by weight of 1.2% sodium silicate aqueous solution, stir and mix, then add 50 parts by weight of silane A151, continue to stir fry until dry, add 20 parts by weight of zinc stearate, continue to stir until well mixed;
[0054] 4) Press the mixture into an iron powder core at a pressure of 10.0T / cm3;
[0055] 5) Heat the iron powder core to 200°C, anneal for 3 hours, cool to room temperature, and vibrate for 45 minutes to remove burrs;
[0056] 6) Spray epoxy resin paint on the iron powder core with a paint film thickness of 0.21 mm to obtain the non-aging iron powder core.
[0057] Example 3
[0058] A method for preparing a non-aging iron powder core comprises the following steps:
[0059] 1) Weigh 350 parts by weight of reduced iron powder, add 40 parts by weight of pure water, and stir to moisten;
[0060] 2) Add 80 parts by weight of a mixed acid solution containing 1.2% phosphoric acid, 0.08% nitric acid and 0.012% oxalic acid, stir evenly, react for 6 hours, and at the same time raise the temperature to 180°C, stir-fry the iron powder until dry;
[0061] 3) Add 60 parts by weight of pure water, stir until fully moistened, then add 2.1 parts by weight of zirconium oxide powder, stir until well mixed, then add 100 parts by weight of 1.5% sodium silicate aqueous solution, stir until well mixed, then add 70 parts by weight of silane A151, continue to stir fry until dry, add 40 parts by weight of zinc stearate, continue to stir until well mixed;
[0062] 4) Pressing the mixture into an iron powder core at a pressure of 12.0T / cm3;
[0063] 5) Heat the iron powder core to 230°C, anneal and heat treat for 4 hours, cool to room temperature and vibrate for 60 minutes to remove burrs;
[0064] 6) Spray epoxy resin paint on the iron powder core, with the paint film thickness of 0.26 mm, to obtain the non-aging iron powder core.
[0065] Comparative Example 1
[0066] According to the method described in Example 1, in step 2), an equal weight of phosphoric acid is used to replace the mixed acid solution, and other parts remain unchanged to prepare an iron powder core as a comparative example 1.
[0067] Comparative Example 2
[0068] According to the method described in Example 1, in step 3), an equal amount of silicon dioxide is used instead of zirconium oxide, and other things remain unchanged to prepare an iron powder core as a comparative example 2.
[0069] Example 4
[0070] The iron powder cores prepared in Examples 1-3 and Comparative Examples 1 and 2 were tested according to GB∕T 19346.1 for 3 times, and the average value was taken. The test results are shown in Table 1.
[0071] Table 1
[0072]
[0073] According to the test data in Table 1, compared with the comparative example, the present application has lower power loss, higher resistivity and magnetic flux density, and can maintain lower inductance quality factor loss during long-term operation at high temperature. It can be seen that the mixed acid solution pretreatment and rare earth oxides help to improve the magnetic properties of the iron powder core that runs for a long time at high temperature, ensure that there is no obvious aging phenomenon due to high temperature, and significantly reduce the loss of the magnetic core, extending the service life of the iron powder core.
[0074] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a high-temperature non-aging iron powder core, characterized in that: It includes the following steps: 1) Weigh the reduced iron powder according to the weight ratio, pour in 40 parts by weight of pure water, and stir to moisten; 2) adding the mixed acid solution to the material obtained after wetting in step 1), stirring evenly, reacting for 6 hours, and at the same time raising the temperature to 180° C., stir-frying the iron powder until dry; 3) Add 60 parts by weight of pure water to step 2), stir to fully moisten, add inorganic high-temperature insulating agent, stir until mixed evenly, then add inorganic high-temperature binder, stir to mix evenly, add organic silane coupling agent, continue to stir until dry, add lubricant, continue to stir until mixed evenly, and obtain a mixture; 4) The mixture obtained in step 3) was heated to 12.0 T / cm 3 The pressure is pressed into an iron powder core; 5) heating the iron powder core obtained in step 4) to 230° C., annealing and heat treating for 4 hours, cooling to room temperature and vibrating and grinding for 60 minutes to remove burrs; 6) Spraying epoxy resin paint on the iron powder core obtained in step 5) with a paint film thickness of 0.26 mm, and obtaining the high-temperature non-aging iron powder core after drying; The high temperature non-aging iron powder core is made from the following raw materials: 350 parts by weight of reduced iron powder, 80 parts by weight of mixed acid solution, 2.1 parts by weight of inorganic high-temperature insulating agent, 100 parts by weight of inorganic high-temperature binder, 70 parts by weight of organic silane coupling agent, and 40 parts by weight of lubricant; The mixed acid solution is composed of 1.2% phosphoric acid, 0.08% nitric acid and 0.012% oxalic acid; the inorganic high temperature insulating agent is zirconium oxide powder; the inorganic high temperature binder is 1.5% sodium silicate aqueous solution; The organic silane coupling agent is silane A151; The lubricant is zinc stearate.